Africa and Globalization Challenges of Governance and Creativity (African Histories and Modernities, 2018)
This book considers the promises and challenges of globalization for Africa. Why have African states been perennially unable to diversify their economies and move beyond export of primary produce, even as Southeast Asia has made a tremendous leap into manufacturing? What institutional impediments are in play in African states? What reforms would mitigate the negative effects of globalization and distribute its benefits more equitably? Covering critical themes such as political leadership, security challenges, the creative sector, and community life, essays in this volume argue that the starting point for Africa's meaningful engagement with the rest of the world must be to look inward, examine Africa's institutions, and work towards reforms that promote inclusiveness and stability.